Pain Management in Athletes With Impairment: A Narrative Review of Management Strategies. Issue 5 (September 2018) - Grobler, Lara; Derman, Wayne; Blauwet, Cheri A.; Chetty, Sean; Webborn, Nick; Pluim, Babette
Abstract : Objective: To review the literature related to different treatment strategies for the general population of individuals with amputation, spinal cord injury, and cerebral palsy, as well as how this may impact pain management in a correlated athlete population. Data Sources: A comprehensive literature search was performed linking pain with terms related to different impairment types. Main Results: There is a paucity in the literature relating to treatment of pain in athletes with impairment; however, it is possible that the treatment strategies used in the general population of individuals with impairment may be translated to the athlete population. There are a wide variety of treatment options including both pharmacological and nonpharmacological treatments which may be applicable in the athlete. Conclusions: It is the role of the physician to determine which strategy of the possible treatment options will best facilitate the management of pain in the individual athlete in a sport-specific setting.